173. Nationwide Outpatient Oral Antimicrobial Utilization by Children in Japan. (26th November 2018) - Kinoshita, Noriko; Morisaki, Naho; Okubo, Yusuke; Uda, Kazuhiro; Kasai, Masashi; Horikoshi, Yuho; Miyairi, Isao
Abstract: Background: Antimicrobial resistance (AMR) is a major public health concern across the world. Japanese government set goals in national AMR action plan to reduce oral cephalosporins, macrolides, and quinolones into a half of the 2013 use by 2020. We evaluated the nationwide antimicrobial use (AMU) of children in Japan using the dispensing receptive from the national administrative database in regard to the national AMR action plan. Methods: The national health claims database was interrogated for oral antibiotics dispensed from outpatient pharmacies in Japan to children under 15 years of age from January 2013 to December 2016. Information obtained from each prescription included age, residence area, days of therapy (DOT) for each antimicrobial from dispensing receptive. DOT was corrected by the resident population in area and calculated as DOT/1, 000 pediatric inhabitants/day (DOT/PID). Chi-squared test for trend was performed to evaluate the annual changes of DOT/PID. Results: A total of 1, 3869, 332 oral antibiotic prescriptions were identified during 2013–2016. Total amount of antimicrobial used in children did not change (2013: 28.54 DOT/PID, 2016: 28.70 DOT/PID, P trend = 0.25). No statistically significant changes were observed in prescriptions of third-generation cephalosporin (2013:10.21DOT/PID, 2016:9.87DOT/PID, P trend = 0.50), macrolide (2013:11.04 DOTID, 2016:10.72 DOT/PID, P trend = 0.52), and quinolone (2013:1.46DOT/PID, 2016:1.86DOT aged <5 years compared with older infants, with the highest rate among children aged 1 year. Targeted antimicrobials for AMR action plan showed similar distribution by age (Figure 2). Conclusion: Interim assessment of the national AMR action plan revealed that the goals were not attainable without significant interventions in children by 2020. Overall antibiotic prescription as well as cephalosporins, macrolides, and quinolones prescription were most prevalent in children aged 1 year. Antimicrobial stewardship targeting infants and younger children is necessary. Disclosures: All authors: No reported disclosures.